(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Damaiyani J, Fiqa AP, Rindyastuti R, Lestari DA, Rahadiantoro A, Yulistyarini T. 2022. Comparative anatomical study of leaves for twelve Indonesian woody plant species. Biodiversitas 23: 3744-3754. Foliar epidermal and stomatal features are widely used as plant microscopic traits either from taxonomic or ecological standpoints. The studies on woody plants in the Malesian region which serve as the essential component of tropical ecosystems are still limited. Here we conduct a comparative study on stomatal and epidermal features of twelve important woody plant species from Indonesia using a descriptive method based on the Light Microscope and Scanning Electron Microscope micrographs. The shape, size and stomatal type were revealed in all species studied. Moreover, quantitative features were measured including epidermal cell length and width, solidity (S), aspect ratio (AR), and stomatal index (SI). The study results showed a variation in foliar epidermal and stomatal traits across the species studied. Due to the presence of trichomes and waxes on the abaxial side, not all species can be measured for their stomatal index and epidermal cells. Syzygium polyanthum has the highest stomatal index and cells with complex interlocking shapes, which provide an effective strategy for reducing mechanical stress on epidermal cell walls, making this native species predicted to adapt well when it was planted in habitats with similar environmental conditions.